MODERN PEDAGOGICAL APPROACH TO THE FORMATION OF PROFESSIONAL SKILLS OF FUTURE PRIMARY SCHOOL TEACHERS (Web of Teachers: Inderscience Research, 2024)
In this article, it is to enrich the experience of primary school teachers on the basis of new approaches to the educational process in the development of modern knowledge, mainly vocational-spiritual.